Learning Science With Group Investigation And Guided Inquiry To Increase Biological Literacy In Coordination System Materials Of Class Science Xi Students - Hariyanti Nenti; Prasetyorini Prasetyorini; Suhardi Eka (Universitas Pakuan, 2021)
The aims of this research are to find out : the effect difference between implementation of cooperative learning model's Group Investigation and type, and Guided Inquiry model's to Increase Biology Literacy , and the effect interaction between implementation of cooperative learning model's and student's on the learning motivation to Increase Biology Literacy. The research was in the Senior High School in the Rancabungur District academic year 2016/2017. The research method used is a quasi-experimental method with a two factorial design. The population of the research is students at the twelth grade Senior High School in the Rancabungur District. The samples of research consist of 80 students. Instruments used for collecting data are achievement test of Biology and the questionnaires of study motivation. To get appropriate and accuracy of the Biology achievement test Technique of t test with significance level of = 0.05. The result of the research are as follows : there is a significant difference in effect of implementation of cooperative learning Group Investigation (GI) and type, and Guided Inquiry model's on Increase Biology Literacy (F h Ft , 0.05 = 2.58 1.99). The questionnaire results showed that students and teacher responded positively to the Group Investigation and Group Inquiry Learning Model. Based on those findings, the research concludes that learning achievement of Biology can be increased throught learning models and improving the student's achievement motivation. The improving of learning quality is able to be achieved through the use of cooperative learning model's Group Investigation and type, and Guided Inquiry model's and by pay attention to the student's Increase Biology Literacy.